Enhancing antifouling property of PVA membrane by grafting zwitterionic polymer via SI-ATRP method. Issue 14 (21st September 2020) - Cui, Mengmeng; Shen, Mingcheng; Zhou, Li; Luo, Zhongkuan; Zhou, Haohao; Yang, Xinlin; Hu, Huiyuan
Abstract: Poly(zwitterions) polymer brushes were fabricated by surface-initiated atom transfer radical polymerization (SI-ATRP) on PVA substrate. The results of XPS and FTIR proved the successful graft of CBMA and SBMA to PVA. The surface of the PVA films would be rougher after the functionalization. Its hydrophilicity increased dramatically and the water contact angle decreased from 45.2° to 7.2°. The visible light transmittance was above 88%. Mechanical properties decreased slightly after grafting, the tensile strength and tensile strain at break were in 1.23-1.85 MPa and 361.7-471.1%, respectively. The anti-protein adsorption performance of the modified PVA film was significantly enhanced and the lowest adsorption amount was up to 2.25 μg/cm 2 . The cytotoxicity grade of modified PVA film was 0-1, which indicated the modified film possessed no cytotoxicity. Additionally, the surface of zwitterion-grafted PVA film had strongly resistance to cell adhesion. All the results confirmed that the zwitterions modified PVA was a promising anti-fouling material for the further biomedical use.